A Review of Recent Advances in the Inhibition of Sweet Corrosion. Issue 7 (24th May 2021) - Xhanari, Klodian; Wang, Yefei; Yang, Zhen; Finšgar, Matjaž
Abstract: This review paper discusses the research work published in the last decade on the use of organic compounds and natural products as corrosion inhibitors for steel in CO2 and CO2 /H2 S coexisting environments. The carbon and mild steel samples tested are mostly immersed in CO2 ‐saturated NaCl/brine solutions or simulated oilfield waters. The influence of temperature, immersion time, CO2 partial pressure, pre‐corrosion, flow rate/rotation speed, and the synergistic effect of other compounds on the corrosion inhibition effectiveness of organic compounds and natural products is presented. Primarily, weight loss and electrochemical techniques were used to evaluate the corrosion inhibition effectiveness of these compounds. Abstract : The most frequently employed organic compounds to inhibit sweet corrosion in the last decade.